Discussion of Dr. Anderson's Case with a Focus on Transference and Countertransference. Issue 1 (1st January 2020) - Leiken, Stanley J.
ABSTRACT: This richly engaging paper offers us the opportunity to closely examine the trauma of early loss, the role of adoption, countertransference variations during latency and adolescence, and to appreciate the long-erm follow-up of an analysis.